Order and disorder arising from alarm: how do termites behave facing potential threats - Cardoso, Luana Dias Leite (2021)
Individuals respond differently to distinct intensities of an alarm signal and that, ulti- mately, could affect group order. Under signals of low intensity, a few individuals are bound to be affected and to respond while the majority would remain doing regular activities. At this point, a high variety of behaviours are observed so that the group is perceived as disordered. As alarm intensity gets higher, a low variety of behaviours and group cohesion may happen, since most individuals would perceive the signal and respond similarly. That in fact is what we aim to show in this work. Here we test the hypothesis that under alarm the order of social groups at individual scale is modulated by the intensity of the signal. Our results support that, under low intensity of the signal, individuals tend to behave uncoordinatedly. Under higher intensity of the signal, the opposite is observed. This happens because under low doses of the stimulus, the diversity of behaviours is increased whereas under high doses the diversity of behaviours decreased as predicted by our hypothesis. Ultimately, a group exhibiting low variety of behaviours correspond to a more cohesive group, or a group exhibiting collective behaviour. It remains to be tested whether even more intense alarm signals, such as risk of predation, would compromise this cohesion, by returning individuals to their idiosyncratic behaviours. Keywords: Order and disorder. Termites. Alarm behaviour.